Sintered body, laminate, and neutron radiation absorbing member and impact absorbing member comprising said sintered body or said laminate

By adding metal element M to the forged body containing tungsten silicon carbide, the problem of insufficient bending strength of the forged body in the prior art is solved, and the bending strength is achieved to achieve a bending strength of 300 MPa or higher.

JP7654418B2Active Publication Date: 2025-04-01MITSUI MINING & SMELTING CO LTD
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
JP2021022095
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-27
Filing Date
2021-02-15
Publication Date
2025-04-01
Estimated Expiration
2041-02-15

AI Technical Summary

Technical Problem

The existing forged bodies containing tungsten silicon carbide have shortcomings in terms of bending strength and are difficult to meet the high-strength needs.

Method used

At least one metal element M, such as aluminum (Al), silicon (Si), tungsten (W), lead (Pb), and iron (Fe) is added to the forged body containing tungsten silicon carbide, to improve its bending strength.

Benefits of technology

By adding metal element M, the bending strength of the tungsten-containing silicon carbide forged body is significantly improved to reach 300 MPa or higher, suitable for high-strength applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654418000003
    Figure 0007654418000003
  • Figure 0007654418000004
    Figure 0007654418000004
  • Figure 0007654418000005
    Figure 0007654418000005
Patent Text Reader

Abstract

To provide a sintered body containing boron carbide having improved flexure strength, a laminate formed by containing the sintered body, and a neutron ray absorption member and an impact absorbing member formed by containing the sintered body or the laminate.SOLUTION: The present invention provides a sintered body containing boron carbide and at least one metal element M1, a sintered body having the flexure strength of 300 MPa or larger, a laminate formed by containing the sintered body, and a neutron beam absorbing member and an impact absorbing member formed including the sintered body or the laminate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sintered body, a laminate, and a neutron radiation absorbing member and an impact absorbing member comprising the sintered body or the laminate. [Background technology]

[0002] Conventionally, sintered bodies containing boron carbide have been known (for example, Patent Documents 1 and 2). Sintered bodies containing boron carbide can exhibit performance such as neutron radiation absorption and impact absorption, and are therefore used as components of neutron radiation absorbing members, impact absorbing members, and the like (for example, Patent Documents 3 to 6). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2-504386 [Patent Document 2] Patent No. 5430869 [Patent Document 3] JP 2001-242288 A [Patent Document 4] JP 2003-167091 A [Patent Document 5] JP 2014-055081 A [Patent Document 6] JP 2014-098524 A Summary of the Invention [Problem to be solved by the invention]

[0004] There is a demand for improved bending strength of sintered bodies containing boron carbide.

[0005] Therefore, an object of the present invention is to provide a sintered body containing boron carbide, which has improved bending strength, a laminate comprising the sintered body, and a neutron beam absorbing member and an impact absorbing member comprising the sintered body or the laminate. [Means for solving the problem]

[0006] In order to solve the above problems, the present invention provides a sintered body containing boron carbide and at least one metal element M1, the sintered body having a bending strength of 300 MPa or more, a laminate including the sintered body, and a neutron beam absorbing member and an impact absorbing member including the sintered body or the laminate. Effect of the Invention

[0007] According to the present invention, there are provided a sintered body containing boron carbide, the sintered body having improved bending strength, a laminate comprising the sintered body, and a neutron beam absorbing member and an impact absorbing member comprising the sintered body or the laminate. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a cross-sectional view of a sintered body according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of the laminate according to the first embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view of a laminate according to a second embodiment of the present invention. [Figure 4] FIG. 4 is a cross-sectional view of a laminate according to a third embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] <Sintered body> The present invention provides a sintered body containing boron carbide and at least one metal element M1, the sintered body having a bending strength of 300 MPa or more. Hereinafter, an embodiment of the sintered body of the present invention will be described.

[0010] The sintered body of the present invention contains boron carbide, which allows the sintered body of the present invention to exhibit properties such as neutron radiation absorption and impact absorption.

[0011] The stoichiometric composition of boron carbide is represented by B4C, but boron carbide may have a composition that deviates from the stoichiometric composition (non-stoichiometric composition). The composition of boron carbide contained in the sintered body of the present invention may be a stoichiometric composition or a non-stoichiometric composition. Examples of boron carbide include B x C(x=3.5~4.5), B 5.26 C, B 5.66 C, B 6.5 C, B7C, B8C, B 25 C, B 12 C2, B 13 C2, B 12 C3, B 14 C, B 6.5 Among these, boron carbides represented by chemical formulas such as B x C(x=3.5~4.5), B 6.5 C, B 12 C 2、 B 14 Boron carbide represented by a chemical formula such as C is preferred. The boron carbide contained in the sintered body of the present invention may be one type or two or more types. Since the X-ray diffraction (XRD) pattern of boron carbide varies depending on the type of boron carbide, the type of boron carbide contained in the sintered body of the present invention can be identified based on the X-ray diffraction pattern of the sintered body of the present invention. The X-ray diffraction pattern of the sintered body of the present invention can be measured using a commercially available X-ray diffraction device.

[0012] The content of boron carbide in the sintered body of the present invention can be appropriately adjusted within a range that allows a bending strength of 300 MPa or more to be realized. From the viewpoint of realizing a bending strength of 300 MPa or more, the content of boron carbide is preferably 10 mass% or more, more preferably 20 mass% or more, and even more preferably 30 mass% or more, based on the mass of the sintered body of the present invention.

[0013] The content of boron carbide in the sintered body of the present invention may be appropriately adjusted in consideration of the performance required for the sintered body of the present invention.

[0014] When the performance required for the sintered body of the present invention is neutron radiation absorbency, the content of boron carbide is preferably 10 mass% or more, more preferably 20 mass% or more, and even more preferably 30 mass% or more, based on the mass of the sintered body of the present invention.

[0015] When the performance required for the sintered body of the present invention is impact absorption, the boron carbide content is preferably 50 mass% or more, more preferably 70 mass% or more, and even more preferably 80 mass% or more, based on the mass of the sintered body of the present invention.

[0016] The upper limit of the content of boron carbide in the sintered body of the present invention is 100% by mass minus the content of the metal element M1. Considering the presence of unavoidable impurities (e.g., C, N, O, etc.), the total of the content of boron carbide and the content of the metal element M1 may actually be less than 100% by mass.

[0017] The content of boron carbide in the sintered body of the present invention may be adjusted so that the sintered body of the present invention has a sea-island structure. When the sintered body of the present invention has a sea-island structure, boron carbide typically constitutes the part that becomes the sea (i.e., the matrix part). In the sea-island structure, the part that becomes the sea exists continuously, and the parts that become the islands are scattered in the form of islands in the part that becomes the sea.

[0018] The content of boron carbide in the sintered body of the present invention can be calculated based on the measured content of boron element by measuring the content of boron element using a conventional method such as inductively coupled plasma atomic emission spectroscopy (ICP-AES). When calculating the content of boron carbide based on the content of boron element, the chemical formula of boron carbide is BC.

[0019] The sintered body of the present invention contains at least one metal element M1. By containing at least one metal element M1 in addition to boron carbide, the sintered body of the present invention can achieve a bending strength of 300 MPa or more.

[0020] The metal element M1 can be appropriately selected within a range that can realize a bending strength of 300 MPa or more. The metal element M1 can be selected from metal elements such as aluminum (Al), silicon (Si), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), yttrium (Y), zirconium (Zr), niobium (Nb), molybdenum (Mo), lead (Pb), cadmium (Cd), cerium (Ce), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), and tungsten (W). These metal elements can be contained in the sintered body for the purpose of further improving the radiation absorption performance of the sintered body and improving the bending strength, heat resistance, oxidation resistance, thermal conductivity, electrical conductivity, etc. of the sintered body.

[0021] From the viewpoint of realizing a bending strength of 300 MPa or more, the metal element M1 is preferably selected from W, Pb, and Fe. W, Pb, and Fe have excellent gamma ray absorption and X-ray absorption. Therefore, when the metal element M1 is selected from W, Pb, and Fe, a bending strength of 300 MPa or more can be realized, and radiation absorption properties such as gamma ray absorption and X-ray absorption can be imparted to the sintered body of the present invention.

[0022] The metal element M1 preferably contains at least one selected from Al and Si in addition to at least one selected from W, Pb, and Fe. Al and / or Si are derived from, for example, a sintering aid. The relative density of the sintered body can be improved by the sintering aid containing Al and / or Si. Examples of the sintering aid include carbides containing Al and / or Si, and in particular, Al x S y C z Preferred is Al4Si1C4, which exists as Al. x S y C zis preferable in that it can improve the relative density of the sintered body and in that it does not react with the solvent, does not decompose in the slurry, and can retain its shape up to the sintering step in the method for producing a sintered body of the present invention described later.

[0023] The metal element M1 may be contained in the sintered body of the present invention in the form of a simple metal, or in the form of an inorganic compound containing the metal element M1. Examples of the inorganic compound include carbides, borides, oxides, and nitrides containing the metal element M1. For example, at least a part of the metal element M1 contained in the sintered body of the present invention may form a carbide and / or a boride.

[0024] The content of the metal element M1 in the sintered body of the present invention can be appropriately adjusted within a range that can realize a bending strength of 300 MPa or more. From the viewpoint of realizing a bending strength of 300 MPa or more, the content of the metal element M1 in the sintered body of the present invention is preferably 7 mass% or more and 800 mass% or less, more preferably 8 mass% or more and 600 mass% or less, and even more preferably 10 mass% or more and 100 mass% or less, based on the content of boron carbide in the sintered body of the present invention. Note that, when the sintered body of the present invention contains one type of metal element M1, the "content of the metal element M1" means the content of the one type of metal element M1, and when the sintered body of the present invention contains two or more types of metal elements M1, the "content of the metal element M1" means the content of the two or more types of metal elements M1.

[0025] When the metal element M1 contains W, the content of W in the sintered body of the present invention is preferably 7.1% by mass or more and 790% by mass or less, more preferably 7.5% by mass or more and 590% by mass or less, and even more preferably 8.0% by mass or more and 90% by mass or less, based on the content of boron carbide in the sintered body of the present invention. In addition, "when the metal element M1 contains W" includes both the case where the sintered body of the present invention contains one type of metal element M1 and W is selected as the one type of metal element M1, and the case where the sintered body of the present invention contains two or more types of metal elements M1 and W is selected as one of the two or more types of metal elements M1. The same applies to "when the metal element M1 contains Al" and "when the metal element M1 contains Si" described later.

[0026] When the metal element M1 contains Al, the Al content in the sintered body is preferably 0.05 mass% or more and 9.0 mass% or less, more preferably 0.1 mass% or more and 5.0 mass% or less, based on the boron carbide content in the sintered body of the present invention.

[0027] When the metal element M1 contains Si, the Si content in the sintered body is preferably 0.01 mass% or more and 2.5 mass% or less, more preferably 0.05 mass% or more and 1.5 mass% or less, based on the boron carbide content in the sintered body of the present invention.

[0028] The content of the metal element M1 in the sintered body of the present invention may be adjusted so that the sintered body of the present invention has a sea-island structure. When the sintered body of the present invention has a sea-island structure, boron carbide typically constitutes the part that becomes the sea (i.e., the matrix part), and the metal element M1 typically constitutes the part that becomes the island. The metal element M1 that constitutes the part that becomes the island may be in the state of a simple metal or in the state of an inorganic compound containing the metal element M1. The explanation regarding the inorganic compound containing the metal element M1 is the same as above.

[0029] The content of the metal element M1 in the sintered body of the present invention can be measured by a conventional method such as inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0030] From the viewpoint of realizing high bending strength, the thickness of the sintered body of the present invention is preferably 0.1 mm to 200 mm, more preferably 0.2 mm to 100 mm, and even more preferably 0.3 mm to 50 mm. When determining the thickness of the sintered body, the thicknesses are measured at three arbitrary points on the cut surface of the sintered body, and the average value of the thicknesses is taken as the thickness of the sintered body.

[0031] The distribution of the metal element M1 in the sintered body of the present invention may be uniform or non-uniform. That is, the sintered body of the present invention may have a concentration gradient of the metal element M1. For example, as shown in FIG. 1, in a layer L composed of the sintered body of the present invention, the concentration of the metal element M1 may decrease from one surface of the layer L to the other surface M2 of the layer L. The presence of a concentration gradient of the metal element M1 in the sintered body of the present invention can be confirmed by measuring the content of the metal element M1 in any two adjacent regions in the thickness direction of the layer L. For example, as shown in FIG. 1, when the layer L is divided into a first portion L1, a second portion L2, and a third portion L3 in order from one surface of the layer L by a plane perpendicular to the thickness direction of the layer L, it can be said that the concentration gradient of the metal element M1 exists in the sintered body of the present invention when the relationship of the content of the metal element M1 in the first portion L1>the content of the metal element M1 in the second portion L2>the content of the metal element M1 in the third portion L3 is established. From the viewpoint of realizing a bending strength of 300 MPa or more, the content of the metal element M1 in the third portion L3, which has the lowest concentration of the metal element M1, is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, and even more preferably 1 mass% or more based on the content of boron carbide in the third portion L3, and the content of the metal element M1 in the first portion L1, which has the highest concentration of the metal element M1, is preferably 800 mass% or less, more preferably 600 mass% or less, and even more preferably 400 mass% or less based on the content of boron carbide in the first portion L1. The preferred range of the content of the metal element M1 in the entire layer L is the same as the preferred range of the content of the metal element M1 in the sintered body of the present invention.

[0032] The total content of boron carbide and metal element M1 in the sintered body of the present invention can be appropriately adjusted within a range that allows a bending strength of 300 MPa or more to be realized. From the viewpoint of realizing a bending strength of 300 MPa or more, the total content of boron carbide and metal element M1 is preferably 70 mass% or more, more preferably 80 mass% or more, and even more preferably 90 mass% or more based on the mass of the sintered body of the present invention.

[0033] The upper limit of the total content of boron carbide and the metal element M1 in the sintered body of the present invention is theoretically 100 mass %, but considering the presence of unavoidable impurities (e.g., C, N, O, etc.), it may actually be less than 100 mass %.

[0034] The sintered body of the present invention has a phase containing boron carbide. The phase containing boron carbide may be a single phase of boron carbide, which is a crystalline phase or an amorphous phase, or may be a solid solution phase of boron carbide and a metal element M1 or a compound thereof (for example, a carbide, a boride, an oxide, or a nitride containing the metal element M1). The sintered body of the present invention may have a phase containing a metal element M1 in addition to a phase containing boron carbide. The phase containing a metal element M1 may be a single phase of a metal element 1 or a compound thereof (for example, a carbide, a boride, an oxide, or a nitride containing the metal element M1), which is a crystalline phase or an amorphous phase, or may be a solid solution phase of a metal element M1 or a compound thereof and boron carbide.

[0035] The bending strength of the sintered body of the present invention is 300 MPa or more. The bending strength is preferably 320 MPa or more, and more preferably 350 MPa or more. The upper limit of the bending strength is not particularly limited. The bending strength is, for example, 700 MPa or less, 500 MPa or less, or 450 MPa or less.

[0036] The bending strength is measured in accordance with the "three-point bending strength test method" specified in JIS R 1601:2008. As a measuring device, for example, an autograph AG-IS manufactured by Shimadzu Corporation can be used. Specific measuring conditions are as described in the examples.

[0037] The relative density of the sintered body of the present invention is not particularly limited, but is preferably 90% or more, more preferably 92% or more, and even more preferably 95% or more.

[0038] The relative density is defined as the percentage of the bulk density of the sintered body to the theoretical density of the sintered body (bulk density of the sintered body / theoretical density of the sintered body × 100). The bulk density of the sintered body (g / cm 3The theoretical density ρ (g / cm 3 ) is the formula: ρ=[(m1 / 100) / ρ1+(m2 / 100) / ρ2+(m3 / 100) / ρ3+ +(m i / 100) / ρ i 〕 -1 In the formula, m1 to m i indicates the content (weight%) of the constituent material of the sintered body, and ρ1 to ρ i are m1 to m i The density of the constituent material (g / cm 3 ) are shown). Specific measurement conditions are as described in the Examples.

[0039] The Vickers hardness of the sintered body of the present invention is not particularly limited, but is preferably 24 GPa or more and 35 GPa or less, more preferably 26 GPa or more and 34 GPa or less, and even more preferably 28 GPa or more and 33 GPa or less.

[0040] The Vickers hardness is measured in accordance with the "Testing method for hardness of fine ceramics" specified in JIS R 1610:2003. The average value of the Vickers hardness at five points is adopted as the Vickers hardness of the sintered body. The Vickers hardness at each point is measured with a test force of 300 gf (2.942 N). The specific measurement conditions are as described in the Examples.

[0041] From the viewpoint of maintaining high rigidity, when the performance required for the sintered body of the present invention is neutron radiation absorption, the thickness of the sintered body of the present invention is preferably 0.1 mm to 200 mm, more preferably 0.2 mm to 100 mm, and even more preferably 0.3 mm to 50 mm, and when the performance required for the sintered body of the present invention is impact absorption, the thickness of the sintered body of the present invention is preferably 0.1 mm to 100 mm, more preferably 0.5 mm to 50 mm, and even more preferably 1 mm to 10 mm. The method for determining the thickness of the sintered body is the same as above.

[0042] The sintered body of the present invention can be produced by molding a slurry containing a raw material powder, drying the obtained molded body, and firing it.

[0043] The raw powder includes a source of boron carbide. The source of boron carbide is preferably a powder of boron carbide. The particle size of the powder of boron carbide can be appropriately adjusted. The median diameter D of the powder of boron carbide 50 From the viewpoints of moldability, densification and uniformity of the structure, etc., the median diameter D is preferably 0.1 μm or more and 5.0 μm or less, more preferably 0.2 μm or more and 4.0 μm or less, and even more preferably 0.2 μm or more and 3.0 μm or less. 50 is the particle size at which the cumulative volume is 50% in the volume-based particle size distribution measured by a laser diffraction / scattering particle size distribution measurement method.

[0044] The raw material powder includes a source of the metal element M1. Examples of the source of the metal element M1 include powder of a simple metal constituted by the metal element M1, a sintering aid, and the like.

[0045] Examples of the solvent used to prepare the slurry include water and organic solvents.

[0046] The slurry can be molded, for example, by slip casting, in which the slurry is poured into a mold (for example, a plaster mold) and the mold absorbs moisture, allowing the slurry to solidify and obtain a molded body.

[0047] Drying and firing of the molded body can be carried out according to a conventional method. The drying temperature is preferably 20°C or more and 150°C or less, more preferably 30°C or more and 100°C or less. The drying time can be appropriately adjusted depending on the size, shape, etc. of the molded body, but when the thickness of the first layer 11 is in the range described later, the drying time can be, for example, 0.5 hours or more and 500 hours or less, 12 hours or more and 250 hours or less, etc. The firing temperature is preferably 1800°C or more and 2350°C or less, more preferably 2000°C or more and 2300°C or less. The firing time can be appropriately adjusted depending on the size of the molded body, the type and size of the furnace, etc., but when the thickness of the first layer 11 is in the range described later, the firing time can be, for example, 3 hours or more and 24 hours or less, 6 hours or more and 18 hours or less, etc. The firing atmosphere may be a vacuum or an inert gas atmosphere such as nitrogen or argon.

[0048] The sintering of the molded body is preferably carried out by heating from room temperature to temperature T1, heating from temperature T1 to temperature T2, and holding at temperature T2. Temperature T1 is preferably 1000°C or more and 1900°C or less, more preferably 1300°C or more and 1800°C or less. The heating time from room temperature to temperature T1 is preferably 5 hours or more and 40 hours or less, more preferably 10 hours or more and 20 hours or less, and the atmosphere during heating from room temperature to temperature T1 is preferably vacuum. Temperature T2 is preferably 2000°C or more and 2350°C or less, more preferably 2100°C or more and 2300°C or less. The heating time from temperature T1 to temperature T2 is preferably 2 hours or more and 40 hours or less, and the atmosphere during heating from temperature T1 to temperature T2 is preferably an inert gas atmosphere such as nitrogen or argon. The holding time at temperature T2 is preferably 3 hours or more and 24 hours or less, more preferably 6 hours or more and 18 hours or less, and the atmosphere during holding at temperature T2 is preferably an inert gas atmosphere such as nitrogen or argon.

[0049] After firing, the arithmetic mean roughness Ra, ten-point mean roughness Rzjis and maximum height Ryjis of at least a part of the surface of the obtained sintered body may be adjusted as necessary. The adjustment of these surface roughness parameters can be performed, for example, by a roughening method such as blasting (also called sandblasting). The blasting can be performed according to a conventional method. Processing conditions such as the material of the abrasive used in the blasting, particle size, injection pressure and processing time can be appropriately selected according to the required surface roughness and the shape of the surface to be treated. For example, when treating a surface of 50 mm square, alumina particles (particle size 1.0 to 500 μm) or the like can be used, and the treatment can be performed under conditions of an injection pressure of 0.1 to 1.2 MPa and a treatment time of 10 to 300 seconds.

[0050] <Laminate> The present invention provides a laminate comprising a first layer and a second layer, the first layer being composed of the sintered body of the present invention. The laminate of the present invention may comprise other layers as long as it comprises the first layer and the second layer. Other layers may or may not be provided between the first layer and the second layer. Hereinafter, an embodiment of the laminate of the present invention will be described based on the drawings.

[0051] First Embodiment As shown in Figure 2, the laminate 1A of the first embodiment comprises a first layer 11 having a first surface S1 and a second surface S2, a second layer 12 provided on the first surface S1 of the first layer 11, and a third layer 13 provided on the second surface S2 of the first layer 11.

[0052] The third layer 13 is an optional layer and can be omitted. Therefore, the present invention also includes an embodiment in which the third layer 13 is omitted from the laminate 1A.

[0053] <1st layer> The first layer 11 is composed of the sintered body of the present invention. This allows the first layer 11 to exhibit performance such as neutron radiation absorption and impact absorption. Therefore, a member including the laminate 1A can be used as, for example, a neutron radiation absorption member, an impact absorption member, etc.

[0054] As shown in FIG. 1, the first layer 11 has a first surface S1 and a second surface S2 located on the opposite side to the first surface S1.

[0055] The arithmetic mean roughness Ra of the first surface S1 of the first layer 11 is preferably 1 μm or more and 30 μm or less, more preferably 1.5 μm or more and 25 μm or less, and even more preferably 2 μm or more and 20 μm or less. This can improve the bonding between the first layer 11 and a layer provided on the first surface S1 of the first layer 11 (the second layer 12 in the first embodiment, and the second layer 12′ in the second and third embodiments described later).

[0056] The ten-point average roughness Rzjis of the first surface S1 of the first layer 11 is preferably 7 μm or more and 150 μm or less, more preferably 8 μm or more and 100 μm or less, and even more preferably 9 μm or more and 60 μm or less. This can further improve the bonding between the first layer 11 and a layer provided on the first surface S1 of the first layer 11 (the second layer 12 in the first embodiment, and the second layer 12' in the second and third embodiments described later).

[0057] The maximum height Ryjis of the first surface S1 of the first layer 11 is preferably 7 μm or more and 200 μm or less, more preferably 8 μm or more and 150 μm or less, and even more preferably 10 μm or more and 90 μm or less. This can further improve the bonding between the first layer 11 and a layer (the second layer 12 in the first embodiment, and the second layer 12′ in the second and third embodiments described later) provided on the first surface S1 of the first layer 11.

[0058] The arithmetic mean roughness Ra of the second surface S2 of the first layer 11 is preferably 1 μm or more and 30 μm or less, more preferably 1.5 μm or more and 25 μm or less, and even more preferably 2 μm or more and 20 μm or less. This can improve the bonding between the first layer 11 and a layer provided on the second surface S2 of the first layer 11 (the third layer 13 in the first embodiment and the second embodiment described later, and the third layer 13' in the third embodiment described later).

[0059] The ten-point average roughness Rzjis of the second surface S2 of the first layer 11 is preferably 7 μm or more and 150 μm or less, more preferably 8 μm or more and 100 μm or less, and even more preferably 9 μm or more and 60 μm or less. This can further improve the bonding between the first layer 11 and a layer provided on the second surface S2 of the first layer 11 (the third layer 13 in the first embodiment and the second embodiment described later, and the third layer 13' in the third embodiment described later).

[0060] The maximum height Ryjis of the second surface S2 of the first layer 11 is preferably 7 μm or more and 200 μm or less, more preferably 8 μm or more and 150 μm or less, and even more preferably 10 μm or more and 90 μm or less. This can further improve the bonding between the first layer 11 and a layer provided on the second surface S2 of the first layer 11 (the third layer 13 in the first embodiment and the second embodiment described later, and the third layer 13' in the third embodiment described later).

[0061] The arithmetic mean roughness Ra, ten-point mean roughness Rzjis and maximum height Ryjis of the first surface S1 and second surface S2 of the first layer 11 can be measured under the following conditions in accordance with JIS B 0601:1994. Measuring equipment: Mitutoyo SURFTEST SJ-210 Measurement range: 16mm Measurement speed: 0.5mm / s Measuring force: 4mN Cutoff λc: 0.8mm Stylus shape: Tip radius 5μm, tip angle 90 degrees Standard: JIS B 0601:1994

[0062] The thickness of the first layer 11 can be adjusted in consideration of the performance required for the first layer 11.

[0063] When the performance required of first layer 11 is neutron radiation absorbency, the thickness of first layer 11 is preferably 0.1 mm or more and 200 mm or less, more preferably 0.2 mm or more and 100 mm or less, and even more preferably 0.3 mm or more and 50 mm or less.

[0064] When the performance required of the first layer 11 is impact absorption, the thickness of the first layer 11 is preferably 0.1 mm or more and 100 mm or less, more preferably 0.5 mm or more and 50 mm or less, and even more preferably 1 mm or more and 10 mm or less.

[0065] When determining the thickness of the first layer 11, the thickness is measured at any three points on the cut surface of the first layer 11, and the average value of these measurements is defined as the thickness of the first layer 11.

[0066] <2nd layer> As shown in FIG. 1, the second layer 12 is provided on a first surface S1 of the first layer 11.

[0067] The second layer 12 can be appropriately selected in consideration of the performance required for the second layer 12. Examples of the performance required for the second layer 12 include radiation resistance, radiation absorption (α-ray absorption, β-ray absorption, γ-ray absorption, X-ray absorption, neutron radiation absorption, etc.), and protection for the first layer 11 (for example, prevention of destruction of the first layer 11, prevention of scattering of fragments generated when the first layer 11 is destroyed, etc.).

[0068] The second layer 12 may be, for example, a ceramic layer, a metal layer, an inorganic compound layer, a resin layer, or the like.

[0069] The ceramic layer is composed of a sintered body containing an inorganic compound, such as an oxide, carbide, boride, or nitride containing a metallic or non-metallic element.

[0070] The ceramic layer is composed of, for example, a sintered body containing boron carbide (hereinafter, for convenience, referred to as the "second sintered body" in order to distinguish it from the sintered body of the present invention constituting the first layer 11). The second sintered body can exhibit performance such as neutron radiation absorption and impact absorption by containing boron carbide. Therefore, the second sintered body is particularly useful when the performance required for the ceramic layer is neutron radiation absorption or impact absorption.

[0071] The composition of boron carbide contained in the second sintered body may be stoichiometric or non-stoichiometric. x C(x=3.5~4.5), B 5.26 C, B 5.66 C, B 6.5 C, B7C, B8C, B 25 C, B 12 C2, B 13 C2, B 12 C3, B 14 C, B 6.5 Among these, boron carbides represented by chemical formulas such as B x C(x=3.5~4.5), B 6.5 C, B 12 C 2、 B 14 C or other chemical formula is preferred. The boron carbide contained in the second sintered body may be one type or two or more types. The type of boron carbide contained in the second sintered body can be identified based on the X-ray diffraction pattern of the sintered body, as in the case of the sintered body of the present invention.

[0072] The content of boron carbide in the second sintered body can be appropriately adjusted in consideration of the performance required for the second layer 12.

[0073] When the performance required of the second sintered body is neutron radiation absorbency, the boron carbide content is preferably 10 mass% or more, more preferably 20 mass% or more, and even more preferably 30 mass% or more, based on the mass of the second sintered body.

[0074] When the performance required of the second sintered body is impact absorption, the boron carbide content is preferably 50 mass% or more, more preferably 70 mass% or more, and even more preferably 80 mass% or more, based on the mass of the second sintered body.

[0075] The upper limit of the boron carbide content in the second sintered body is theoretically 100% by mass, but considering the presence of unavoidable impurities (for example, C, N, O, etc.), it may actually be less than 100% by mass.

[0076] The content of boron carbide in the second sintered body may be adjusted so that the second sintered body has a sea-island structure. When the second sintered body has a sea-island structure, boron carbide typically constitutes the sea portion (i.e., the matrix portion).

[0077] The content of boron carbide in the second sintered body can be calculated based on the measured content of boron element by measuring the content of boron element using a conventional method such as inductively coupled plasma atomic emission spectrometry (ICP-AES). When calculating the content of boron carbide based on the content of boron element, the chemical formula of boron carbide is B4C.

[0078] The second sintered body may contain one or more elements (hereinafter referred to as "other elements") other than the elements constituting boron carbide (that is, carbon atoms and boron atoms).

[0079] The other elements can be appropriately selected taking into consideration the performance required for the second layer 12.

[0080] The second sintered body may contain, for example, at least one metal element M2. The metal element M2 may be selected from metal elements such as aluminum (Al), silicon (Si), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), yttrium (Y), zirconium (Zr), niobium (Nb), molybdenum (Mo), lead (Pb), cadmium (Cd), cerium (Ce), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), and tungsten (W), but is preferably selected from W, Pb, Fe, Al, and Si.

[0081] W, Pb and Fe have excellent gamma ray absorption and X-ray absorption properties. Therefore, when the metal element M2 is selected from W, Pb and Fe, the second sintered body can be given radiation absorption properties such as gamma ray absorption and X-ray absorption.

[0082] Al and / or Si are derived from, for example, a sintering aid. By including a sintering aid containing Al and / or Si in the second sintered body, the relative density of the second sintered body can be improved. Examples of the sintering aid include carbides containing Al and / or Si, and in particular, Al x S y C z Preferred is Al4Si1C4, which exists as Al. x S y C z is preferable in that it can improve the relative density of the second sintered body, and in that it does not react with the solvent, does not decompose in the slurry, etc., in the manufacturing method of the second sintered body, and can retain its shape up to the sintering step.

[0083] In one embodiment, the metal element M2 includes at least one selected from W, Pb, and Fe. In another embodiment, the metal element M2 includes at least one selected from Al and Si. In yet another embodiment, the metal element M2 includes at least one selected from W, Pb, and Fe, and at least one selected from Al and Si.

[0084] The metal element M2 may be contained in the second sintered body in the form of a simple metal, or in the form of an inorganic compound containing the metal element M2. Examples of the inorganic compound include carbides, borides, oxides, and nitrides containing the metal element M2. For example, at least a part of the metal element M2 contained in the second sintered body may form a carbide and / or a boride.

[0085] The content of the metal element M2 in the second sintered body can be appropriately adjusted in consideration of the performance required for the second layer 12. The content of the metal element M2 in the second sintered body is preferably smaller than the content of the metal element M1 in the sintered body of the present invention. By making the content of the metal element M2 in the second sintered body smaller than the content of the metal element M1 in the sintered body of the present invention, the above-mentioned performance can be imparted without impairing the strength of the second sintered body. The content of the metal element M2 in the second sintered body is preferably less than 7.0 mass%, more preferably 5.0 mass% or less, and even more preferably 3.0 mass% or less, based on the mass of the second sintered body. The lower limit of the content of the metal element M2 in the second sintered body is not particularly limited. The content of the metal element M2 in the second sintered body is, for example, more than 0 mass%, 0.5 mass% or more, or 1.0 mass% or more, based on the mass of the second sintered body. In addition, the "content of metal element M2" means the content of one metal element M2 when the second sintered body contains one metal element M2, and means the content of two or more metal elements M2 when the second sintered body contains two or more metal elements M2. The same applies to the "case where metal element M2 contains Al" and the "case where metal element M2 contains Si" described later.

[0086] When the metal element M2 contains Al, the content of Al in the second sintered body is preferably 0.05 mass % or more and 9.0 mass % or less, and more preferably 0.1 mass % or more and 5.0 mass % or less, based on the mass of the sintered body.

[0087] When the metal element M2 contains Si, the content of Si in the second sintered body is preferably 0.01 mass % or more and 2.5 mass % or less, more preferably 0.05 mass % or more and 1.5 mass % or less, based on the mass of the sintered body.

[0088] The content of the metal element M2 in the second sintered body may be adjusted so that the second sintered body has a sea-island structure. When the second sintered body has a sea-island structure, boron carbide typically constitutes the part that becomes the sea (i.e., the matrix part), and the metal element M2 typically constitutes the part that becomes the island. The metal element M2 that constitutes the part that becomes the island may be in the state of a simple metal or in the state of an inorganic compound containing the metal element M2. The explanation regarding the inorganic compound containing the metal element M2 is the same as above.

[0089] The content of the metal element M2 in the second sintered body can be measured by a common method such as inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0090] The second sintered body has a phase containing boron carbide. The phase containing boron carbide may be a single phase of boron carbide, which is a crystalline phase or an amorphous phase, or may be a solid solution phase of boron carbide and another element (e.g., metal element M2) or a compound thereof (e.g., a carbide, a boride, an oxide, or a nitride containing metal element M2). When the second sintered body contains another element, the sintered body may have a phase containing the other element in addition to the phase containing boron carbide. The phase containing the other element may be a single phase of another element (e.g., metal element M2) or a compound thereof (e.g., a carbide, a boride, an oxide, or a nitride containing metal element M2), which is a crystalline phase or an amorphous phase, or may be a solid solution phase of the other element or a compound thereof and boron carbide.

[0091] The sintered body of the present invention may be used as the second sintered body.

[0092] The thickness of the ceramic layer can be appropriately adjusted in consideration of the performance required for the ceramic layer. When the performance required for the ceramic layer is radiation absorption, the thickness of the ceramic layer is preferably 0.1 mm to 200 mm, more preferably 0.2 mm to 100 mm, and even more preferably 0.3 mm to 50 mm. When determining the thickness of the ceramic layer, the thickness is measured at any three points on the cut surface of the ceramic layer, and the average value of these measurements is taken as the thickness of the ceramic layer.

[0093] The ceramic layer can be formed on the first surface S1 of the first layer 11 according to a conventional method. For example, the slurry for forming the first layer is molded by casting or the like, then the slurry for forming the second layer is added onto the molded body of the slurry for forming the first layer, molded by casting or the like, and then the laminate of the molded body of the slurry for forming the first layer and the molded body of the slurry for forming the second layer is dried and fired, thereby forming the ceramic layer on the first surface S1 of the first layer 11. Preparation and molding of the slurry, drying and firing of the molded body, etc. can be performed in the same manner as for the sintered body of the present invention.

[0094] The metal layer is composed of a metal element. Examples of the metal element that constitutes the metal layer include aluminum, tungsten, lead, iron, zinc, copper, silver, gold, nickel, titanium, and alloys thereof. Aluminum has excellent β-ray absorption, and tungsten, lead, and iron have excellent γ-ray absorption and X-ray absorption. Therefore, a metal layer composed of these metal elements is particularly useful when the performance required for the metal layer is radiation absorption. In addition, gold, silver, platinum, iron, nickel, copper, aluminum, zinc, tin, lead, and the like have excellent ductility, and the material is difficult to break and deforms flexibly. Therefore, a metal layer composed of these metal elements is particularly useful when the performance required for the metal layer is the protective property of the first layer (for example, the ability to prevent the first layer 11 from being destroyed, the ability to prevent fragments from scattering when the first layer 11 is destroyed, etc.).

[0095] The metal layer may have a single layer structure or a laminated structure. The materials constituting the two or more layers constituting the laminated structure may be the same or different. An example of the laminated structure is a two-layer structure composed of an aluminum metal layer and a tungsten metal layer. In this two-layer structure, it is preferable that the aluminum metal layer is located on the first surface S1 side of the first layer 11 in terms of improving adhesion between the first layer 11 and the metal layer.

[0096] The thickness of the metal layer can be appropriately adjusted in consideration of the performance required for the metal layer. When the performance required for the metal layer is radiation absorption, the thickness of the metal layer is preferably 0.1 mm to 50 mm, more preferably 0.1 mm to 20 mm, and even more preferably 0.1 mm to 10 mm. When determining the thickness of the metal layer, the thickness is measured at any three points on the cut surface of the metal layer, and the average value of the thicknesses is taken as the thickness of the metal layer.

[0097] The metal layer can be formed by a common method on the first surface S1 of the first layer 11. Examples of methods for forming the metal layer include a PVD method (sputtering method, vacuum deposition method, ion plating method, etc.), a CVD method, a casting method, a pressing method, a thermal spraying method, etc.

[0098] The inorganic compound layer is composed of an inorganic compound. Examples of inorganic compounds constituting the inorganic compound layer include compounds containing inorganic elements such as aluminum, tungsten, lead, iron, magnesium, titanium, sodium, lithium, calcium, potassium, lanthanoid, vanadium, and chromium. Examples of compounds containing inorganic elements include oxides, carbides, borides, and nitrides containing inorganic elements such as aluminum, tungsten, lead, iron, and silicon; and metal-based hydrides or complex-based hydrides containing inorganic elements such as magnesium, titanium, sodium, lithium, calcium, potassium, lanthanoid, vanadium, and chromium. Compounds containing aluminum may be referred to as "aluminum compounds" below. The same applies to compounds containing other inorganic elements. Aluminum compounds have excellent β-ray absorption, and tungsten compounds, lead compounds, and iron compounds have excellent γ-ray absorption and X-ray absorption. Therefore, inorganic compound layers composed of these inorganic compounds are particularly useful when the performance required for the inorganic compound layer is radiation absorption.

[0099] The thickness of the inorganic compound layer can be appropriately adjusted in consideration of the performance required for the inorganic compound layer. When the performance required for the inorganic compound layer is radiation absorption, the thickness of the inorganic compound layer is preferably 0.1 mm to 50 mm, more preferably 0.1 mm to 20 mm, and even more preferably 0.1 mm to 10 mm. When determining the thickness of the inorganic compound layer, the thicknesses of three arbitrary points on the cut surface of the inorganic compound layer are measured, and the average value of the thicknesses is taken as the thickness of the inorganic compound layer.

[0100] The inorganic compound layer may have a single layer structure or a laminated structure. The materials constituting the two or more layers constituting the laminated structure may be the same or different. An example of the laminated structure is a two-layer structure composed of an aluminum compound layer and a tungsten compound layer. In this two-layer structure, it is preferable that the aluminum compound layer is located on the first surface S1 side of the first layer 11 in terms of improving adhesion between the first layer 11 and the inorganic compound layer.

[0101] The inorganic compound layer can be formed by a common method on the first surface S1 of the first layer 11. Examples of methods for forming the inorganic compound layer include a PVD method (sputtering method, vacuum deposition method, ion plating method, etc.), a CVD method, a casting method, a pressing method, a thermal spraying method, etc.

[0102] The resin layer contains a resin as a main component. The term "main component" means that the content of the resin is 20% by mass or more based on the mass of the resin layer. The content of the resin is preferably 30% by mass or more, more preferably 40% by mass or more based on the mass of the resin layer. The resin may be a thermoplastic resin or a cured resin. The thermoplastic resin can be appropriately selected from known thermoplastic resins. The cured resin is a cured product of a curable resin, and examples of the curable resin include thermosetting resins. The thermosetting resin can be appropriately selected from known thermosetting resins. The resin layer may contain one or more additives. Examples of the additives include a polymerization inhibitor, a crosslinking agent, an antistatic agent, an adhesion improver, an antioxidant, a leveling agent, a thixotropic agent, a coupling agent, a plasticizer, an antifoaming agent, a filler, a catalyst, a curing agent (including a crosslinking agent, a polymerization initiator, a polymerization accelerator, etc.), and the like.

[0103] The resin that is the main component of the resin layer may have radiation resistance. Examples of resins that have radiation resistance include polyethylene, polypropylene, polyimide, polyetherimide, polyetheretherketone, polyester, polyurethane, polyethylene terephthalate, vinylidene fluoride, etc. Resin layers that contain these resins as the main components are particularly useful when the performance required for the resin layer is radiation resistance (for example, when a member including the laminate 1A is used as a neutron beam absorbing member).

[0104] The resin that is the main component of the resin layer may have radiation absorbing properties. Examples of resins that have radiation absorbing properties include polyethylene, polypropylene, polyester, polyurethane, and polyethylene terephthalate. A resin layer that is mainly composed of these resins is particularly useful when the performance required for the resin layer is radiation absorbing properties (for example, when a member including the laminate 1A is used as a neutron absorbing member). Among these resins, polyethylene has a high hydrogen density (amount of hydrogen per unit volume) and high neutron absorbing properties. Therefore, a resin layer that is mainly composed of polyethylene is particularly useful when the performance required for the resin layer is neutron absorbing properties (for example, when a member including the laminate 1A is used as a neutron absorbing member).

[0105] The resin that is the main component of the resin layer may be composited with a material for imparting light weight, high strength, impact absorption, etc. That is, the resin layer may be formed of a composite material of the main component resin and other materials. Examples of materials that are composited with the main component resin to impart high strength include glass fiber, carbon fiber, fibrous or film-like resins (e.g., aromatic polyamide resins (aramid resins), polyparaphenylene benzobis oxazole resins, high-density polyethylene resins, etc.), and various inorganic fillers (e.g., silica, alumina, zirconia, barium sulfate, etc.).

[0106] The resin layer may have a single-layer structure or a laminated structure. The materials constituting the two or more layers constituting the laminated structure may be the same or different.

[0107] The thickness of the resin layer can be appropriately adjusted in consideration of the performance required for the resin layer. When the performance required for the resin layer is radiation absorbency, the thickness of the resin layer is preferably 2 mm or more and 500 mm or less, more preferably 5 mm or more and 200 mm or less, and even more preferably 10 mm or more and 100 mm or less. When determining the thickness of the resin layer, the thicknesses of three arbitrary points on the cut surface of the resin layer are measured, and the average value of the measured thicknesses is taken as the thickness of the resin layer.

[0108] The resin layer can be formed on the first surface S1 of the first layer 11 according to a conventional method. Examples of the method for forming the resin layer include a coating method, a printing method, and a compression molding method. Examples of the coating method include a roll coating method, a knife coating method, an air knife coating method, a die coating method, a lip coating method, a comma coating method, a kiss coating method, a flow coating method, and a dip coating method. Examples of the printing method include a gravure printing method, an offset printing method, a screen printing method, a flexographic printing method, an electrostatic printing method, and an inkjet printing method.

[0109] <3rd layer> As shown in FIG. 1, the third layer 13 is provided on the second surface S2 of the first layer 11.

[0110] The third layer 13 can be appropriately selected in consideration of the performance required for the third layer 13. Examples of the performance required for the third layer 13 include radiation resistance, radiation absorption (α-ray absorption, β-ray absorption, γ-ray absorption, X-ray absorption, neutron radiation absorption, etc.), and protection for the first layer 11 (for example, prevention of destruction of the first layer 11, prevention of scattering of fragments generated when the first layer 11 is destroyed, etc.).

[0111] Examples of the third layer 13 include a ceramic layer, a metal layer, an inorganic compound layer, a resin layer, etc. The ceramic layer, the metal layer, the inorganic compound layer, and the resin layer can be described in the same manner as in the second layer 12.

[0112] <Second embodiment> As shown in Figure 2, the laminate 1B of the second embodiment comprises a first layer 11 having a first surface S1 and a second surface S2, a second layer 12' provided on the first surface S1 of the first layer 11, a third layer 13 provided on the second surface S2 of the first layer 11, and a fourth layer 14 provided on a surface T1 of the second layer 12' opposite the first layer 11.

[0113] The third layer 13 is an optional layer and can be omitted. Therefore, the present invention also includes an embodiment in which the third layer 13 is omitted from the laminate 1B.

[0114] The first layer 11 is composed of the sintered body of the present invention, and can exhibit performance such as neutron radiation absorption and impact absorption. Therefore, a member including the laminate 1B can be used as, for example, a neutron radiation absorption member, an impact absorption member, etc.

[0115] In the laminate 1B, the same members as those in the laminate 1A (for example, the first layer 11 and the third layer 13) are denoted by the same reference numerals as those in the laminate 1A. The explanation of the same members as those in the laminate 1A is the same as that for the laminate 1A. The following describes the differences between the laminate 1B and the laminate 1A.

[0116] <2nd layer> As shown in FIG. 2, the second layer 12' is provided on the first surface S1 of the first layer 11.

[0117] The second layer 12' is an adhesive layer that bonds the first layer 11 and the fourth layer 14 together.

[0118] The adhesive layer is made of an adhesive. Examples of the adhesive constituting the adhesive layer include an acrylic adhesive, a rubber adhesive, a silicone adhesive, a urethane adhesive, an α-olefin adhesive, an ether adhesive, an ethylene-vinyl acetate resin adhesive, an epoxy resin adhesive, a vinyl chloride resin adhesive, a chloroprene rubber adhesive, a cyanoacrylate adhesive, an aqueous polymer-isocyanate adhesive, a styrene-butadiene rubber adhesive, a nitrile rubber adhesive, a nitrocellulose adhesive, a reactive hot melt adhesive, a phenolic resin adhesive, a modified silicone adhesive, a polyamide resin adhesive, and a polyimide adhesive. Examples of the adhesive include a polyurethane resin adhesive, a polyolefin resin adhesive, a polyvinyl acetate resin adhesive, a polystyrene resin solvent adhesive, a polyvinyl alcohol adhesive, a polyvinylpyrrolidone resin adhesive, a polyvinyl butyral resin adhesive, a polybenzimidazole adhesive, a polymethacrylate resin adhesive, a melamine resin adhesive, a urea resin adhesive, a resorcinol adhesive, and the like, of which modified silicone adhesives, epoxy resin adhesives, acrylic adhesives, silicone adhesives, cyanoacrylate adhesives, polyurethane resin adhesives, and the like are preferred. Note that the adhesive layer constituted by these adhesives corresponds to the resin layer.

[0119] The thickness of the adhesive layer can be adjusted as appropriate. The thickness of the adhesive layer is preferably 0.001 mm or more and 10 mm or less, more preferably 0.001 mm or more and 5 mm or less, and even more preferably 0.001 mm or more and 3 mm or less. When determining the thickness of the adhesive layer, the thickness is measured at any three points on the cut surface of the adhesive layer, and the average value of the measured thicknesses is taken as the thickness of the adhesive layer.

[0120] The adhesive layer can be formed by a conventional method on the first surface S1 of the first layer 11. Examples of a method for forming the adhesive layer include a coating method and a printing method.

[0121] <4th layer> As shown in FIG. 2, the fourth layer 14 is provided on a surface T1 of the second layer 12' opposite to the first layer 11.

[0122] The fourth layer 14 can be appropriately selected in consideration of the performance required for the fourth layer 14. Examples of the performance required for the fourth layer 14 include radiation resistance, radiation absorbency (α-ray absorbency, β-ray absorbency, γ-ray absorbency, X-ray absorbency, neutron absorbency, etc.), and protection for the first layer 11 (for example, prevention of destruction of the first layer 11, prevention of scattering of fragments generated when the first layer 11 is destroyed, etc.).

[0123] Examples of the fourth layer 14 include a ceramic layer, a metal layer, an inorganic compound layer, a resin layer, etc. The ceramic layer, the metal layer, the inorganic compound layer, and the resin layer are the same as those in the first embodiment (the second layer 12).

[0124] The fourth layer 14 may be manufactured as a separate member according to a conventional method, and then laminated on the first surface S1 of the first layer L1 via the second layer 12'. The ceramic layer, metal layer, and inorganic compound layer may be manufactured as separate members according to a conventional method such as casting, metal press processing, and powder metallurgy. The resin layer may be manufactured as a separate member, for example, by casting. In casting, the resin is thoroughly mixed, injected into a desired mold, and cured to manufacture the resin layer as a separate member. In addition to casting, it is also possible to use general resin molding methods such as injection molding, extrusion molding, blow molding, vacuum molding, and compression molding. After molding, strength may be improved by after-baking or the like.

[0125] <Third embodiment> As shown in Figure 3, the laminate 1C of the third embodiment comprises a first layer 11 having a first surface S1 and a second surface S2, a second layer 12' provided on the first surface S1 of the first layer 11, a third layer 13' provided on the second surface S2 of the first layer 11, a fourth layer 14 provided on a surface T1 of the second layer 12' opposite to the first layer 11, and a fifth layer 15 provided on a surface T2 of the third layer 13' opposite to the first layer 11.

[0126] The first layer 11 is composed of the sintered body of the present invention, and can exhibit performance such as neutron radiation absorption and impact absorption. Therefore, a member including the laminate 1C can be used as, for example, a neutron radiation absorption member, an impact absorption member, etc.

[0127] In the laminate 1C, the same members as those in the laminate 1B (for example, the first layer 11, the second layer 12', and the fourth layer 14) are denoted by the same reference numerals as those in the laminate 1B. The explanation of the members that are the same as those in the laminate 1B is the same as that in the laminate 1B. The following describes the differences between the laminate 1C and the laminate 1B.

[0128] <3rd layer> As shown in FIG. 3, the third layer 13' is provided on the second surface S2 of the first layer 11.

[0129] The third layer 13' is an adhesive layer that bonds the first layer 11 and the fifth layer 15. The explanation regarding the adhesive layer is the same as the explanation in the second embodiment (the explanation in the second layer 12').

[0130] <5th layer> As shown in FIG. 3, the fifth layer 15 is provided on a surface T2 of the third layer 13' opposite to the first layer 11.

[0131] The fifth layer 15 can be appropriately selected in consideration of the performance required for the fifth layer 15. Examples of the performance required for the fifth layer 15 include radiation resistance, radiation absorbency (α-ray absorbency, β-ray absorbency, γ-ray absorbency, X-ray absorbency, neutron ray absorbency, etc.), and protection for the first layer 11 (for example, prevention of destruction of the first layer 11, prevention of scattering of fragments generated when the first layer 11 is destroyed, etc.).

[0132] Examples of the fifth layer 15 include a ceramic layer, a metal layer, an inorganic compound layer, a resin layer, etc. The ceramic layer, the metal layer, the inorganic compound layer, and the resin layer are the same as those in the second embodiment (the fourth layer 14). EXAMPLES

[0133] Example 1 A slurry was prepared by mixing 100 parts by mass of boron carbide powder (average particle size 0.6 μm, specific gravity 2.5, manufactured by HC Starck), 1 to 10 parts by mass of carbon black (average particle size 80 nm, manufactured by Mitsubishi Carbon Black), 8 parts by mass of tungsten metal powder, and 40 to 100 parts by mass of water. The obtained slurry was poured into a 50 mm square plaster mold and subjected to slip casting. After leaving it for 6 hours, it was demolded and dried to obtain a molded body having a thickness of 10 mm.

[0134] The obtained molded body was fired under the following conditions. Heating from 20℃ to 1800℃ (under vacuum): 9 hours Heating from 1800℃ to 2250℃ (under Ar gas atmosphere): 2 hours Holding at 2250℃ (under Ar gas atmosphere): 6 hours

[0135] The density of the obtained sintered body (g / cm 3 ), relative density (%), Vickers strength (GPa) and flexural strength (MPa) were measured as follows.

[0136] Density of sintered body (g / cm 3 ) was measured in accordance with JIS R 1634:1998.

[0137] The relative density (%) of the sintered body was calculated based on the formula: bulk density of the sintered body / theoretical density of the sintered body × 100. 3 ) was measured in accordance with JIS R 1634:1998. Theoretical density of the sintered body (g / cm 3 ) is expressed by the formula: Theoretical density of sintered body = [(m1 / 100) / ρ1 + (m2 / 100) / ρ2 + (m3 / 100) / ρ3 + + (m i / 100) / ρ i 〕 -1 The calculation was based on the following formula: i indicates the content (weight%) of the constituent material of the sintered body, and ρ1 to ρ i are m1 to m i The density of the constituent material (g / cm 3 ) indicates.

[0138] After mirror finishing of the sintered body test pieces, the Vickers hardness (GPa) was measured according to the "hardness test method for fine ceramics" specified in JIS R 1610:2003. The average value of the Vickers hardness at five points was taken as the Vickers hardness of the sintered body. The Vickers hardness at each point was measured with a test force of 300gf (2.942N).

[0139] The sintered body was processed into a test piece as specified in JIS R 1601: 2008, and the obtained test piece was used to perform a bending strength test at room temperature in accordance with the "three-point bending strength test method" as specified in JIS R 1601: 2008, and the bending strength (MPa) of the test piece was measured. The measurement device used was an autograph AG-IS manufactured by Shimadzu Corporation.

[0140] Data for Example 1 are shown in Tables 1A and B.

[0141] Example 2 The slurry was prepared in the same manner as in Example 1, except that the amount of tungsten metal powder was changed from 8 parts by mass to 12 parts by mass. Data for Example 2 are shown in Tables 1A and 1B.

[0142] Example 3 The slurry was prepared in the same manner as in Example 1, except that the amount of tungsten metal powder was changed from 8 parts by mass to 700 parts by mass. Data for Example 3 are shown in Tables 1A and 1B.

[0143] Example 4 The same procedure as in Example 1 was carried out to prepare the slurry, except that 10 parts by weight of iron metal powder was used instead of 8 parts by weight of tungsten metal powder, and the sintering temperature was changed from 2250° C. to 2050° C. Data for Example 4 are shown in Tables 1A and 1B.

[0144] Example 5 The same procedure as in Example 1 was carried out, except that the slurry was prepared using 10 parts by weight of lead metal powder instead of 8 parts by weight of tungsten metal powder, and the sintering temperature was changed from 2250° C. to 2050° C. Data for Example 5 are shown in Tables 1A and 1B.

[0145] Example 6 In preparing the slurry, the amount of tungsten metal powder was changed from 8 parts by mass to 9 parts by mass, and a laminate was formed of a 10 mm thick compact and another 10 mm thick compact, and the obtained laminate was fired, except for the same operation as in Example 1. The data for Example 6 are shown in Tables 1A and 1B.

[0146] The formation of the laminate was carried out as follows. A molded body having a thickness of 10 mm was manufactured in the same manner as in Example 1, and this was used as the first layer. 100 parts by mass of boron carbide powder (average particle size 0.6 μm, specific gravity 2.5, manufactured by HC Starck), 1 to 10 parts by mass of carbon black (average particle size 80 nm, manufactured by Mitsubishi Carbon Black), and 40 to 100 parts by mass of water were mixed to prepare a slurry for forming the second layer. The obtained slurry for forming the second layer was poured into a 50 mm square plaster mold containing the first layer (i.e., the plaster mold before the first layer was released) and cast molding was carried out. After leaving it for 6 hours, it was released and dried to obtain a laminate of a molded body having a thickness of 10 mm (first layer) and another molded body having a thickness of 10 mm (second layer).

[0147] Example 7 The same operation as in Example 6 was carried out, except that 100 parts by mass of boron carbide powder, 1 to 10 parts by mass of carbon black, 3 parts by mass of tungsten metal powder, and 40 to 100 parts by mass of water were mixed to prepare a slurry for forming the second layer. The data for Example 7 are shown in Tables 1A and 1B.

[0148] Example 8 In preparing the slurry, the amount of tungsten metal powder is changed from 8 parts by mass to 10 parts by mass, and the slurry containing different amounts of tungsten metal powder is prepared, and the slurry containing the higher concentration is cast in order to form a concentration gradient of tungsten element, so that the operation is the same as that of Example 1. The data of Example 8 are shown in Tables 1A and B.

[0149] Example 9 The slurry was prepared in the same manner as in Example 1, except that the amount of tungsten metal powder was changed from 8 parts by mass to 100 parts by mass. Data for Example 9 are shown in Tables 1A and 1B.

[0150] Example 10 The slurry was prepared in the same manner as in Example 1, except that the amount of tungsten metal powder was changed from 8 parts by mass to 400 parts by mass. Data for Example 10 are shown in Tables 1A and 1B.

[0151] Example 11 The slurry was prepared in the same manner as in Example 4, except that the amount of iron metal powder was changed from 10 parts by weight to 100 parts by weight. Data for Example 11 are shown in Tables 1A and 1B.

[0152] Example 12 The slurry was prepared in the same manner as in Example 4, except that the amount of iron metal powder was changed from 10 parts by weight to 700 parts by weight. Data for Example 12 are shown in Tables 1A and 1B.

[0153] Example 13 The slurry was prepared in the same manner as in Example 5, except that the amount of lead metal powder was changed from 10 parts by mass to 100 parts by mass. Data for Example 13 are shown in Tables 1A and 1B.

[0154] Example 14 The slurry was prepared in the same manner as in Example 5, except that the amount of lead metal powder was changed from 10 parts by mass to 700 parts by mass. Data for Example 14 are shown in Tables 1A and 1B.

[0155] Example 15 The same operation as in Example 1 was carried out, except that Al4SiC4 was used as a sintering aid, and a slurry was prepared by mixing 100 parts by mass of boron carbide powder (average particle size 0.6 μm, specific gravity 2.5, manufactured by HC Starck), 1 to 10 parts by mass of carbon black (average particle size 80 nm, manufactured by Mitsubishi Carbon Black), 8 parts by mass of tungsten metal powder, 1 part by mass of aluminum silicon carbide (Al4SiC4, manufactured by Tateho Chemical Co., Ltd.), and 40 to 100 parts by mass of water. The data for Example 15 are shown in Tables 1A and 1B.

[0156] Comparative Example 1 The slurry was prepared in the same manner as in Example 1, except that the amount of tungsten metal powder was changed from 8 parts by mass to 2 parts by mass. Data regarding Comparative Example 1 are shown in Tables 1A and 1B.

[0157] Comparative Example 2 The slurry was prepared in the same manner as in Example 1, except that the amount of tungsten metal powder was changed from 8 parts by mass to 900 parts by mass. Data regarding Comparative Example 2 are shown in Tables 1A and 1B.

[0158] Comparative Example 3 The slurry was prepared in the same manner as in Example 1, except that 5 parts by mass of lead metal powder was used instead of 8 parts by mass of tungsten metal powder. The data for Comparative Example 3 are shown in Tables 1A and 1B.

[0159] Comparative Example 4 In preparing the slurry, the amount of tungsten metal powder is changed from 8 parts by mass to 10 parts by mass, and the slurry is spray-dried by a spray dryer to obtain a powder, and the powder is uniaxially pressed by a mechanical press method instead of casting to obtain a molded body. The data of Comparative Example 4 are shown in Tables 1A and 1B.

[0160] [Table 1A]

[0161] [Table 1B]

[0162] As shown in Tables 1A and B, in Examples 1 to 8, sintered bodies containing boron carbide and W, Pb or Fe and having a bending strength of 300 MPa or more were obtained. [Explanation of symbols]

[0163] 1A, 1B, 1C...Laminate 11...1st layer 12,12'...2nd layer 13,13'...3rd layer 14...4th layer 15...5th layer S1: First surface of first layer S2: Second surface of the first layer

Claims

1. Boron carbide and at least one metal element M 1 A sintered body comprising: The bending strength is 300 MPa or more, Metal element M 1 contains W, A sintered body, the W content being 12 mass% or more and 100 mass% or less based on the boron carbide content.

2. A sintered body as described in claim 1, having a boron carbide content of 10 mass% or more, based on the mass of the sintered body.

3. A sintered body as described in claim 1, having a boron carbide content of 70 mass% or more, based on the mass of the sintered body.

4. Boron carbide and at least one metal element M 1 A sintered body comprising: The bending strength is 300 MPa or more, Metal element M 1 contains Fe, A sintered body having a boron carbide content of 30 mass% or more based on the mass of the sintered body.

5. A sintered body as described in claim 4, wherein the Fe content is 7 mass% or more based on the boron carbide content.

6. A sintered body as described in claim 4, wherein the Fe content is 7 mass% or more and 100 mass% or less, based on the boron carbide content.

7. A sintered body containing boron carbide and at least one metal element M 1 , The bending strength is 300 MPa or more, A sintered body, wherein the metal element M 1 contains Pb.

8. The sintered body described in claim 7, wherein the Pb content is 7 mass% or more and 800 mass% or less, based on the boron carbide content.

9. A sintered body as described in claim 7 or 8, wherein the boron carbide content is 10 mass% or more based on the mass of the sintered body.

10. The sintered body according to any one of claims 1 to 9, having a relative density of 90% or more.

11. The sintered body according to any one of claims 1 to 10, having a Vickers hardness of 24 GPa or more and 35 GPa or less.

12. Metal element M 1 The sintered body according to any one of claims 1 to 11, wherein at least a portion of the above forms a carbide and / or a boride.

13. The sintered body is composed of a phase containing boron carbide and a metal element M 1 The sintered body according to any one of claims 1 to 12, having a phase comprising:

14. A laminate comprising a first layer and a second layer, A laminate, wherein a first layer is composed of the sintered body according to any one of claims 1 to 13.

15. The laminate according to claim 14, wherein the second layer is composed of a sintered body containing boron carbide.

16. The sintered body constituting the second layer contains at least one metal element M 2 The laminate according to claim 15, comprising:

17. In the sintered body constituting the second layer, the metal element M 2 The laminate according to claim 16, wherein the content of is less than 7.0 mass % based on the content of boron carbide.

18. A neutron absorbing member comprising the sintered body according to any one of claims 1 to 13 or the laminate according to any one of claims 14 to 17.

19. An impact absorbing member comprising the sintered body according to any one of claims 1 to 13 or the laminate according to any one of claims 14 to 17.

Citation Information

Patent Citations

  • JP1975091006A

  • Inspecting method of minute spherical bodies

    JP1979030869A

  • Super hard alloy composition

    JP1985039145A

  • Al2o3-b4c-based high-density calcined compact and production thereof

    JP1990243559A

  • Using the substrate boron carbide / boron carbide and titanium diboride composite production of ceramic powder composition

    JP1990504386A